Dari Teller ke Aplikasi: Transformasi Komunikasi Layanan Perbankan Digital melalui Pengalaman Nasabah myBCA - Ferdian Ardani Putra; Ahmad Fauzi; Gilang Ibnu Ramadani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2025)
Digital transformation is driving significant changes in banking service communications, particularly through the use of mobile banking applications. One such innovation is the myBCA application developed by PT Bank Central Asia Tbk. This study aims to analyze customer experiences with the transformation of digital banking service communications through the use of the myBCA application at the BCA Trunojoyo Jember Branch Office. This study uses a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. Research informants consisted of active myBCA users and service staff at the BCA Trunojoyo Jember Branch Office, who were selected purposively. Data analysis was conducted using the Miles and Huberman interactive model. The results show that the transformation of digital service communications through myBCA provides a positive experience for customers, especially in aspects of ease of use, time efficiency, quality of service interactions, and trust in data security. However, this study also found the need for increased digital education and the development of service features to make digital communications more inclusive and responsive.